Developing Theory Through Simulation Methods - Davis, Jason P.; Eisenhardt, Kathleen M.; Bingham, Christopher B. (Academy of Management Review, 2007)
We describe when and how to use simulation methods in theory development. We develop a roadmap that describes theory development using simulation and position simulation in the “sweet spot” between theory-creating methods, such as multiple case inductive studies and formal modeling, and theory-testing methods. Simulation strengths include internal validity and facility with longitudinal, nonlinear, and process phenomena. Simulation's primary value occurs in creative experimentation to produce novel theory. We conclude with evaluation guidelines.